A Possible Future of Repertories and Software Tools - van Grinsven, Eduard (Homœopathic Links, 2018)
Traditional repertories were originally very useful, but are nowadays becoming too large for practical use in the future. Software and centralised databases could provide a solution in the future, based on statistical relationships between remedies and cases.
Keywords: Repertories; Software; Future; Statistics